2018
DOI: 10.29252/ijrm.16.6.379
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in protamine 1 and 2 genes in asthenozoospermic men: A case-control study

Abstract: Background:Asthenozoospermia is one of the etiologies for male factor infertility. It was shown that any abnormality in protamines genes, reduction of protamines transcript and protamines deficiency may play a key role in asthenozoospermia.Objective:The aim of the current study was the evaluation of protamine-1 and 2 genes (PRM1 and PRM2) polymorphisms in asthenozoospermic men.Materials and Methods: In this case-control study, the samples were corresponded to asthenozoospermic specimens of infertile men. The n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Table 1 presentations the features of studies entered to the meta-analysis. The studies [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] were published from 2003 to 2019. Twelve studies 23,[26][27][28][29][30][31]33,35,[37][38][39] were reported in Caucasian, four studies 24,32,34,36 in Asian, and one 25 in mixed ethnicities.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Table 1 presentations the features of studies entered to the meta-analysis. The studies [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] were published from 2003 to 2019. Twelve studies 23,[26][27][28][29][30][31]33,35,[37][38][39] were reported in Caucasian, four studies 24,32,34,36 in Asian, and one 25 in mixed ethnicities.…”
Section: Resultsmentioning
confidence: 99%
“…The studies [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] were published from 2003 to 2019. Twelve studies 23,[26][27][28][29][30][31]33,35,[37][38][39] were reported in Caucasian, four studies 24,32,34,36 in Asian, and one 25 in mixed ethnicities. The genotyping method was PCR-based in fourteen studies [23][24][25][26][27][28][29][30][31]33,35,[37][38][39] and Mass ARRAY in three studies 32,34,36…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations